Visualisation in Archaeology: Connecting Research and Practice. - Garry Gibbons (Virtual Archaeology Review)
Visualisation in Archaeology (www.viarch.org.uk) is a three-year research project funded by English Heritage. Established in December 2007, Visualisation in Archaeology (VIA) has as its principal mission a commitment to providing a forum in which practitioners and researchers can contribute towards a critical (re)assessment of visualising data resulting from archaeological research. This paper will present an overview of the VIA’s research aims and objectives, its methodology, and its proposed future directions.